2021
DOI: 10.1017/cjn.2021.507
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Correlates of Visual and Minor Hallucinations in Parkinson’s Disease

Abstract: Introduction: Psychosis is one of the incapacitating nonmotor symptoms of Parkinson’s disease (PD). Although several risk factors that include older age, rapid eye movement sleep behavior disorder, depression, and cognitive dysfunction have been identified, the exact neural correlates remain elusive. As cognitive impairment has a close association with psychosis in PD, it is useful to know the spectrum of cognitive impairment in PD patients with psychosis (PD-P). Methods: This cross-sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 29 publications
(34 reference statements)
2
2
0
Order By: Relevance
“…Despite the fact that total mean MoCA scores were relatively similar between patients with and without psychotic manifestations, by analyzing the individual items of MoCA scale, poorer performance in executive, visuospatial, naming and abstraction domains was revealed in patients with PD-associated psychotic symptoms (p < 0.05). This is in accordance with recent literature findings [42]. Visual hallucinations have been associated with multidomain cognitive dysfunction in PD including deficits in executive function [43], sustained attention [44] and visuospatial-perceptual functions [45].…”
Section: Discussionsupporting
confidence: 93%
“…Despite the fact that total mean MoCA scores were relatively similar between patients with and without psychotic manifestations, by analyzing the individual items of MoCA scale, poorer performance in executive, visuospatial, naming and abstraction domains was revealed in patients with PD-associated psychotic symptoms (p < 0.05). This is in accordance with recent literature findings [42]. Visual hallucinations have been associated with multidomain cognitive dysfunction in PD including deficits in executive function [43], sustained attention [44] and visuospatial-perceptual functions [45].…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with previous studies reporting visuo‐spatial impairments in LBD patients with VH 19,20,22,32 as well as in LBD patients with isolated MVH 38,39 . While previous studies have found visuo‐spatial impairments on other VOSP subtests (Dot Counting 20 and Position Discrimination 19 ), only one other recent study reported finding similar impairments specifically on the VOSP CA in LBD patients with VH 54 .…”
Section: Discussionsupporting
confidence: 93%
“…There is considerable previous evidence of impaired performance of LBD patients with VH on the Stroop test 24,25,30,63,64 . Consistent with our findings, LBD patients with isolated MVH have not been found to be impaired on the Stroop test 38 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations